Fermented Non-Digestible Fraction of Andean Berry (Vaccinium meridionale Swartz) Juice Induces Apoptosis in Colon Adenocarcinoma Cells (2020)
ABSTRACT: Vaccinium meridionale Swartz, known as Andean berry, has a high content of anthocyanins, phenolic acids, and other flavonoids due to their putative anticancer activity. However, after consumption, the structures and function of these molecules may be altered. The purpose of this study was to evaluate the pro-apoptotic effect of fermented non-digestible fraction (FNDF) of Andean berry juice (ABJ) on colon adenocarcinoma HT29 cells. HT29 cells were treated by FNDF-ABJ obtained by in vitro gastrointestinal fermentation. We determined the proapoptotic capacity by terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assays, oxidative stress by analyzing superoxide dismutase and catalase activity, lipid peroxidation by measuring 8-iso-prostaglandin F2, and measured lactate dehydrogenase. Our results show that FNDF-ABJ inhibited cell growth [lethal dose 50(%)=26% v/v]. In addition, FNDF-ABJ increased the number of TUNEL positive cells 2-fold compared with untreated cells without altering the release of lactate dehydrogenase. However, superoxide dismutase activity was reduced in HT29 cells treated with FNDF-ABJ, catalase activity was not affected and 8-iso-prostaglandin F2 levels were increased. These results support that the anti-proliferative effects of FNDF-ABJ on HT29 cells can be explained by apoptotic mechanisms.